2017
DOI: 10.12775/eq.2017.005
|View full text |Cite
|
Sign up to set email alerts
|

Biomass of Scots pine-silver birch tree stand 25 years after afforestation of former agricultural land

Abstract: Scots pine (Pinus sylvestris L.), silver birch (Betula pendula Roth) and several seedlings of the European beech-after many years of agricultural cultivation of grain and potato crops. Characteristics of the forest stand comprised the following parameters: species composition and species diversity, density of individual components, the average tree diameter at breast height (DBH), and the height and aboveground biomass of trees divided into individual species. The species structure, dendrometric characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, it should be noted that the broad‐leaved tree silver birch ( Betula pendula Roth ) and the needle‐leaved tree Scot pine ( Pinus sylvestris L . ), which are regarded as low isoprene emitters, were the dominant species for European afforestation (Deptula et al, ); hence, the actual increment of isoprene emission should be much lower than the value derived from the work of Lathière et al (). A net increase of about 4% in Germany and France was contributed by both broad‐leaved and needle‐leaved trees.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, it should be noted that the broad‐leaved tree silver birch ( Betula pendula Roth ) and the needle‐leaved tree Scot pine ( Pinus sylvestris L . ), which are regarded as low isoprene emitters, were the dominant species for European afforestation (Deptula et al, ); hence, the actual increment of isoprene emission should be much lower than the value derived from the work of Lathière et al (). A net increase of about 4% in Germany and France was contributed by both broad‐leaved and needle‐leaved trees.…”
Section: Resultsmentioning
confidence: 96%
“…Lathière et al (2006) concluded that European isoprene emission was significantly affected by European afforestation with an isoprene emission increase of 126% from 1983 to 1995, since crops were substituted with temperate broadleaf evergreen trees resulting in the enhancement of isoprene emission capacity by a factor of 9. However, it should be noted that the broadleaved tree silver birch (Betula pendula Roth) and the needle-leaved tree Scot pine (Pinus sylvestris L.), which are regarded as low isoprene emitters, were the dominant species for European afforestation (Deptula et al, 2017); hence, the actual increment of isoprene emission should be much lower than the value derived from the work of Lathière et al (2006). A net increase of about 4% in Germany and France was contributed by both broad-leaved and needle-leaved trees.…”
Section: Effect Of Afforestation On Isoprene Emission In China Indiamentioning
confidence: 99%
“…The afforestation of former agricultural land is a process that has received considerable socioeconomic attention in recent years [1][2][3][4][5][6][7][8]. Since the energy from renewable resources has been widely promoted, the production of large quantities of easily accessible and useable highly energetic biomass from trees has gained attention, leading to the publication of numerous research papers on the ecological processes for modelling such ecosystems (e.g., [9][10][11][12][13][14][15][16][17][18][19][20]).…”
Section: Introductionmentioning
confidence: 99%
“…A study of the Czech and foreign literature has revealed that there are basically no studies in which the results could be compared with. Focus on other plantings with different parameters of height and trunk diameter, e.g., Jelínek, Úradníček [37] and Deptula et al [22];  Focus on the relation between mortality or vitality to another specific factor (specific nutrients in the soil, mode of seedling production in a nursery, shading, etc. ), e.g., Dostálek et al [29] and Tužimský et al [44];  Do not cover shrubs, as presented in Jelínek [34].…”
Section: Discussionmentioning
confidence: 99%
“…This method is often applied for afforestation of farmland with the aim to establish economically managed forest stands. This topic is covered by a number of research papers, e.g., by Nizinski [16], Friedrichsdorf [17], Bartoš and Kacálek [18], Jylhä and Hytönen [19], Leugner [20], Vacek et al [21] and Deptula et al [22]. Forestry method of establishing woody stands is also used in the reclamation of land after mining and mineral extraction.…”
Section: Introductionmentioning
confidence: 99%